THE LINGUOCULTURAL POTENTIAL OF THE CONCEPT OF “BREAD” IN THE PRACTICE OF TEACHING RUSSIAN AS A FOREIGN LANGUAGE - kizi, Abdusamieva Dilshoda Abduxamid (Research Focus International Scientific Journal, 2026)
This study is devoted to a comparative analysis of the concept of “bread” in Russian and Uzbek linguocultures. The article examines the features of its linguocultural significance, its reflection in the linguistic worldview, and its role in shaping the value systems of the representatives of the two cultures. Particular attention is paid to the analysis of nominations proverbs, and phraseological units associated with the concept of “bread,” which demonstrate its importance in both the everyday and spiritual life of the peoples. The relevance of the study is determined by the need for an in-depth examination of the national and cultural specificity of languages in the context of intercultural communication and foreign language teaching. The comparative approach makes it possible to identify both common and culture-specific features in the perception of the concept of “bread” in Russian and Uzbek cultures.